Peningkatan Keterampilan dan Rasa Percaya Diri Anak melalui Kegiatan Lomba Edukatif di Lingkungan Masyarakat Desa Galeso - A. Muh. Akbar; Muh Ramli (Pusat Penelitian dan Pengabdian kepada Masyarakat (PPPM) Institut Teknologi dan Bisnis Muhammadiyah Polewali Mandar, 2026)
Abstrak: This community service activity aims to enhance the skills and self-confidence of children in Galeso Village through the implementation of educational competitions that actively involve the community. Children are the nation’s most valuable assets and require special attention during their developmental stages, especially in the golden age period, which plays a crucial role in shaping their character and potential. Based on observations, children in Galeso Village tend to have limited access to educational and social activities, highlighting the need for programs that can stimulate their cognitive, affective, and social abilities. Educational competitions such as drawing contests, poetry reading, and educational games were conducted as a means to foster courage, creativity, and self-confidence among children in a healthy competitive environment. The results of the program showed an increase in enthusiasm and participation among children, along with strong support from parents and the community. The children appeared more confident in performing in public, collaborating in groups, and expressing their opinions. In addition to providing a fun learning experience, the activity also strengthened social relationships among children, parents, and the community. Overall, this program has had a positive and sustainable impact on character development in Galeso Village.